NEED FOR VALUE EDUCATION AS AN INTEGRAL PART OF SUSTAINABLE EDUCATION - Rajevska, Feliciana; Kūkoja, Katrīne (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
For a peaceful world and society, it is essential for cultures to be developed and transformed through common values, and value education is one of the main ways to do that since core values are formed from an early age. But when society is going through a radical transformation process as it is in the case of Latvia, it is difficult to avoid anomie when different and conflicting ideas, memories and norms exist in society.The aim of the research is to explore and analyse the tendencies of the main values in the society of Latvia across different age groups, to see how the situation has developed and what are the main values that need to be stressed through value education in the ongoing educational reform process. To reach the aim of the research, a literature review as well as the analysis of the European Social Survey (2008 and 2018) data was conducted.The research results show some shift in values of the society in Latvia mainly due to priorities of younger generation in the period from 2008 to 2018: universal values have replaced self-direction values as the third most common value in the society of Latvia. In the case of younger generations value perception is indefinite. Partly this is due to the lack of focus on values in our education system since the restoration of independence. There is a need to strengthen the motivational values connected with conformity, self-direction, stimulation and universalism (tolerance) through value education. It is desirable to highlight the values of achievement such as creativity and desire to succeed, as they are essential for the knowledge society and stimulate motivation for entrepreneurship.